Beyond multiple choice: measuring troubleshooting skills in networking courses using packet tracer - Zainol, Zarina; Ahmad, Siti Arpah; Harun, Nurzalina; Endut, Nor Adora (Penerbit UiTM (UiTM Press), 2026)
Troubleshooting is a critical skill for network engineers, yet traditional assessments often fail to capture students’ ability to diagnose and resolve faults in realistic scenarios. This study explores the use of Cisco Packet Tracer as a platform for skill-based assessment of troubleshooting competence. An intermediate network topology was developed with five deliberately injected errors, covering VRRP misconfiguration, routing protocol mismatch, ACL filtering, VTP domain inconsistency, and RBAC privilege restriction. Undergraduate students in a networking course attempted to identify and resolve all connectivity issues within Packet Tracer. Student performance was evaluated using the simulation’s automatic scoring engine and structured observation of troubleshooting strategies. Results indicated that while most students eventually restored full functionality, many relied on trial and error, whereas those who used systematic diagnostic methods were more efficient and accurate. Student feedback confirmed that the activity was both challenging and authentic, and most participants supported its inclusion. in future courses. The study concludes that Packet Tracer provides a valid, scalable, and engaging means of assessing troubleshooting skills, while also highlighting the pedagogical importance of emphasizing structured diagnostic frameworks in network education.